Obtenção e caracterização de biocompósitos de fécula de mandioca, fibra de sisal e cera de carnaúba - Gomes, Áleft Verlanger Rocha Gomes (2019)
Concern for sustainable development has provided significant improvements in the creation of biodegradable materials. Among these, the biocomposites has been highlighted since they can be removed without harming the environment and are an alternative to synthetic polymer matrices of composites that are dangerous, biorecalcitrantes and have aggressive effects on human health. Therefore, the purpose of this study was to evaluate the properties of cassava starch biocomposites, carnauba wax and sisal fibers in different compositions. The biocomposites were obtained by the casting process and were subsequently cut into specimens by means of which the absorbed moisture and the apparent density were calculated, and tensile tests were carried out in order to obtain the mechanical properties. A Scanning Electron Microscopy was performed on the fractured surfaces of the specimens. An analysis of X-ray diffraction was conducted in order to verify the variation of the relative crystallinity of the different biocomposites. Representative models of the response surfaces were obtained for the different properties. The addition of sisal fiber increased mechanical properties and reduced density. The addition of carnauba wax improved barrier properties by reducing absorbed moisture, while glycerol had an adverse effect. An increase in the percentage of sisal fiber and carnauba wax provided an increase in the crystallinity of the biocomposite, while increasing the percentage of glycerol reduced crystallinity.